2009
DOI: 10.1063/1.3116624
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium oxide/germanium oxynitride gate stacks on germanium: Capacitance scaling and interface state density

Abstract: Articles you may be interested inComprehensive study and design of scaled metal/high-k/Ge gate stacks with ultrathin aluminum oxide interlayers Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Some literature reported that in situ Ge plasma nitridation for ALD high-k thin film deposition can improve the interface quality [9,18,33]. However, there is rare work on fabrication of the Gebased MOS device with sub-nanometer CET by in situ Ge plasma nitridation.…”
Section: Resultsmentioning
confidence: 97%
“…Some literature reported that in situ Ge plasma nitridation for ALD high-k thin film deposition can improve the interface quality [9,18,33]. However, there is rare work on fabrication of the Gebased MOS device with sub-nanometer CET by in situ Ge plasma nitridation.…”
Section: Resultsmentioning
confidence: 97%
“…The previously published data use a variety of gate oxides and substrates, which could affect both the reported D it and TDD values. 7,8,10,16,[43][44][45][46][47] Hence, the device structure is indicated alongside each data point. An interesting pattern emerges for Ge devices on Si using different epitaxial integration schemes and an Al 2 O 3 /GeO x gate stack: an almost linear increase in D it with increasing TDD.…”
Section: Benchmarking D It As a Function Of Dislocation Densitymentioning
confidence: 99%
“…1 The main problem for the application of Ge is the effective surface passivation before the deposition of the gate dielectric. 2 Many attempts have been proposed to solve this problem such as introducing sulfurization, 3 NH 3 plasma, 4 thermal oxidation, 5-7 H 2 /N 2 / Ar plasma, 8 atomic O, 9 ozone, 10 and so on for the Ge surface passivation. Among all these techniques, the introduction of an interlayer (IL) formed by GeO 2 gave the lowest density of interface states (D it ) and highest comprehensive performance.…”
Section: CMmentioning
confidence: 99%